Junguian hermeneutics: Essays on the early symbolism of the narratives of São João do Guarani - Oliveira, Rannife (2023)
The study of religion from a Jungian perspective has been expanding in Brazil. The Jungian hermeneutic method is still little known. Thus, the article is characterized as theoretical, gathering important concepts in Jungian psychology, explaining how the symbolic hermeneutic method works, and discussing new methodological perspectives in Jungian research in dialogue with the contemporary world. The study also deals with the theme of religion, providing key concepts about the sacred. The results/analysis are related to the method of symbolic amplification of the narratives of São João do Guarani, a popular saint of the forest, worshipped in the Chico Mendes extractive reserve in Xapuri, Acre state. Mythical and symbolic metaphors are then applied to the narratives, considering the conceptual issue of archetype and collective unconscious, evoking the primary analogies and images that the tales produce.